Hedge hunters : how hedge fund masters survived - Burton, Katherine, 1962- (Bloomberg Press, 2010)
"A rare look at the hedge fund industry's top performers that introduces the most talented new managers, handpicked by the masters themselves. With unprecedented candor and detail, the most successful hedge fund managers reveal their personal journeys, their individual strategies for producing outstanding returns, attributes most important to the job, and how they survived the subprime crisis"--Provided by publisher